A high-strength and high-biocompatibility tough hydrogel and a preparation method and application thereof
By repeatedly stretching in sulfate solution and soaking in PBS solution, combined with 3D printing technology, a high-strength, highly biocompatible, and tough hydrogel was prepared. This solved the problems of insufficient biocompatibility and ease of use of existing hydrogels, enabling the use of high-strength and biocompatible hydrogels for tissue repair and drug delivery.
Patent Information
- Application Number
- CN202310734725.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2025-12-05
- Estimated Expiration
- 2043-06-20
AI Technical Summary
Existing tough hydrogels are insufficient in terms of biocompatibility, biodegradability and ease of preparation, making it difficult to meet the actual needs of tissue repair and drug delivery.
A high-strength, highly biocompatible, and tough hydrogel was prepared by repeatedly stretching it in a sulfate solution and immersing it in a PBS solution. Combined with 3D printing technology, an anisotropic structure was formed, which improved the strength and biocompatibility of the hydrogel.
The prepared hydrogel has significantly improved tensile strength, good biocompatibility, can be naturally degraded in vivo, is suitable for tissue repair and drug delivery, and is easy to operate and low in cost.
Smart Images

Figure HDA0004295432830000011 
Figure HDA0004295432830000021 
Figure HDA0004295432830000031
Abstract
Description
Technical Field
[0001] This invention belongs to the field of tissue engineering and biomanufacturing technology under biomedical engineering, and specifically relates to a high-strength, highly biocompatible, tough hydrogel, its preparation method, and its application. Background Technology
[0002] Tough hydrogels have been a major research focus for decades due to their excellent mechanical properties, and they have been widely used in fields such as soft artificial muscles, tissue engineering scaffolds, and flexible electronic devices.
[0003] To obtain tough hydrogels, many new methods have been proposed, such as using a tough double-network hydrogel made of alginate, polyacrylamide, calcium ions, and chitosan. This hydrogel can be directly applied to damaged tendons as an adhesive layer for tendon repair. In another study, a self-healing hydrogel was prepared from substances such as gelatin-methacryloyl (GelMA), hyaluronic acid, and polycaprolactone, which can be used as a protective layer to repair damaged tendons in rats. Furthermore, calcium silicate nanofibers and alginate have also been used to obtain composite hydrogels with biomimetic reinforcing structures. These composite hydrogels significantly promote tissue regeneration from bone to tendon in vivo, especially in fibrocartilage transition tissue.
[0004] Researchers have developed tough hydrogels using various strategies, but these materials differ significantly from human skin, brain, and other organs. Therefore, these tough hydrogels cannot be implanted into the body for medical applications such as tissue engineering and drug delivery. Traditional strategies offer good biocompatibility, unique structures, and high strength, but these hydrogels are often non-degradable and unsuitable for tissue repair. Furthermore, their preparation methods are relatively complex, and the lengthy preparation time limits their efficient application; poor consistency and the need for multiple materials also pose challenges for clinical application.
[0005] Therefore, it is necessary to provide a novel and simple method for preparing a tough hydrogel with good biocompatibility and components that meet the needs of actual tissue repair. Summary of the Invention
[0006] To address the problems existing in the prior art, this invention provides a high-strength, highly biocompatible, and resilient hydrogel and its preparation method. This method is simple to operate, has low additional cost, and is applicable to various hydrogels, demonstrating strong versatility. The resilient hydrogel (GBTH) prepared by this method has high tensile strength, good biocompatibility, and can be naturally degraded in vivo. It can be directly sutured to the site of tendon rupture in adult rabbits to compensate for the mechanical transmission after tendon rupture. The tensile strength of GBTH reaches 6.67 MPa, which is 145 times that of untreated gel (initial hydrogel). Combining this preparation method with 3D printing technology, customized anisotropic resilient hydrogel scaffolds can be fabricated. The resulting scaffolds achieve a tensile strength of 6.5547 MPa, which is 612 times that of untreated 3D-printed hydrogel scaffolds. When applied to damaged tissue, the resilient hydrogel of this invention can stimulate cell differentiation into tendon cells, achieving faster and better tendon regeneration.
[0007] A method for preparing a high-strength, highly biocompatible, and tough hydrogel, comprising:
[0008] The hydrogel was repeatedly stretched in a sulfate solution and then immersed in a PBS solution. The end of the immersion was considered as one loading process. The hydrogel was cyclically loaded multiple times according to the above loading process to obtain the high-strength, highly biocompatible, and tough hydrogel.
[0009] In the above preparation method, the loading process is similar to the human self-training process, during which muscle fiber strength increases, and the hydrogel's molecular chains rearrange along the axial load direction, increasing the degree of molecular chain order and crystallinity. The action of the sulfate solution is similar to the accumulation of lactic acid in the human self-training process, which, according to the Hofmesister effect, occurs in SO42-. 2- Under the influence of [unclear], the initial hydrogel underwent phase separation between the aqueous and gel phases after several cycles of stretching in sulfate solution, promoting molecular chain orientation, and the degree of phase separation gradually increased with increasing stretching time; subsequently, the stretch-trained hydrogel was immersed in PBS solution, at which point SO4 [unclear]... 2- The ions are replaced by water molecules, ensuring biocompatibility.
[0010] Inspired by human self-training, the method for preparing the tough hydrogel of this invention utilizes the synergistic effect of cyclic loading and sulfate solution. By repeatedly stretching, the hydrogel molecular chains are arranged along the stretching direction, thereby positioning the gel molecular chains. At the same time, anisotropic high-functional crystalline regions are generated to prevent cracks from propagating into deeper layers of the hydrogel, thus achieving the preparation of a tough hydrogel. During the stretching process, the stretched hydrogel is soaked in PBS solution at appropriate times to release salt ions and prepare for the next training.
[0011] This invention provides a method for preparing a high-strength, highly biocompatible, and tough hydrogel, which overcomes the limitations of traditional tough hydrogels that cannot simultaneously achieve good biocompatibility, direct implantation into the body for medical applications such as tissue engineering and drug delivery, high strength, and simple preparation process, and has great commercial value.
[0012] Preferably, the hydrogel is stretched repeatedly in the sulfate solution 10 to 30 times during a loading process. More preferably, it is stretched 15 to 25 times. Even more preferably, it is stretched 18 to 22 times.
[0013] Preferably, during a loading process, the hydrogel is immersed in the PBS solution for 30–180 s. More preferably, it is 50–100 s. Even more preferably, it is 60 s.
[0014] Preferably, the concentration of the sulfate solution is 40-60%. More preferably, it is 45-55%. Even more preferably, it is 50%.
[0015] Preferably, the sulfate solution includes, but is not limited to, one or more mixtures of sulfate solutions. More preferably, it is an ammonium sulfate solution.
[0016] As a preferred embodiment, the sulfate solution is a 50% ammonium sulfate solution.
[0017] Preferably, the hydrogel includes, but is not limited to, gelatin (such as methacrylamide gelatin), hyaluronic acid, etc. More preferably, methacrylamide gelatin.
[0018] Preferably, the hydrogel is subjected to 1 to 30 cycles. More preferably, 10 to 25 cycles. Even more preferably, 20 cycles.
[0019] Preferably, the stretching rate of the hydrogel in the sulfate solution is 2–7 mm / min. More preferably, it is 5 mm / min.
[0020] Preferably, the hydrogel exhibits a maximum tensile deformation of 100% in sulfate solution.
[0021] Preferably, the hydrogel is a cured hydrogel or an uncured hydrogel;
[0022] When the hydrogel is an uncured hydrogel, after multiple cycles of loading, the treated hydrogel is cross-linked and cured to obtain the high-strength, highly biocompatible, and tough hydrogel.
[0023] In other words, the preparation process of the tough hydrogel of the present invention can be a cyclic loading process of a solidified hydrogel, or a process of cyclic loading and then solidifying an unsolidified hydrogel.
[0024] The preparation methods of the hydrogel include, but are not limited to, mold casting, photopolymerization additive manufacturing, and extrusion additive manufacturing. As a further preferred embodiment, the hydrogel is prepared by mold casting or extrusion additive manufacturing.
[0025] Preferably, the main components of the PBS solution are a mixture of Na2HPO4, KH2PO4, NaCl and KCl.
[0026] Preferably, the temperature at which the hydrogel is repeatedly stretched in the sulfate solution and the immersion temperature in the PBS solution are each independently selected from 20–30°C. More preferably, the temperature is 24–26°C.
[0027] As a preferred embodiment, a method for preparing a high-strength, highly biocompatible, and tough hydrogel includes the following steps:
[0028] Step 1: The prepared hydrogel precursor solution is poured into a pre-prepared mold and then cured by ultraviolet light to form the initial hydrogel, or 3D printing technology (photopolymerization additive manufacturing, extrusion additive manufacturing) is used to prepare a 3D printed hydrogel scaffold to form the initial hydrogel.
[0029] Step 2: Add the sulfate solution to the tough hydrogel circulating stretching training tank beforehand;
[0030] Step 3: Place the initial hydrogel prepared in Step 1 into a sulfate solution and perform cyclic stretching (repeated stretching) reinforcement training 10-30 times;
[0031] Step 4: After completing the reinforcement training, soak the hydrogel in PBS buffer for 30-180 seconds and then remove it;
[0032] Step 5: Repeat steps 3 and 4 1 to 30 times to complete the cyclic loading and obtain the tough hydrogel.
[0033] The preparation method of this invention involves repeatedly stretching the hydrogel in a sulfate solution and immersing it in PBS buffer to obtain a highly ordered, highly crystalline, anisotropic, high-strength, and highly biocompatible tough hydrogel. Furthermore, it can be combined with 3D printing technology to fabricate customized high-strength, highly biocompatible repair scaffolds. When applied to tissue engineering and regenerative medicine research, the tough hydrogel can achieve mechanical compensation of force transmission. Due to its significant toughness, biocompatibility, in vivo self-degradability, and similarity to natural tissue components, it can be directly sutured onto ruptured tendons in adult rabbits, completing tendon tissue repair within 8 weeks. Additionally, liquid metal can be injected into it for testing on various parts of the human body.
[0034] The method for preparing high-strength, highly biocompatible, and tough hydrogels of the present invention achieves a combination of high-strength hydrogels and high biocompatibility. The method is simple and easy to operate, providing a new approach for tissue regeneration and drug delivery.
[0035] A high-strength, highly biocompatible, and tough hydrogel is prepared by any of the preparation methods described above.
[0036] Preferably, the water content of the tough hydrogel is 50-95%. This can be controlled by adjusting the concentration of the sulfate solution and / or the number of cyclic loading cycles. More preferably, the water content of the tough hydrogel is 60-80%.
[0037] Preferably, the tough hydrogel has a compensating force transmission function in the tensile deformation range of 0-100%, and even more preferably, the tensile deformation for compensating force transmission function is 50% and 100%.
[0038] In this invention, tensile strength is used as an indicator for evaluating tough hydrogels, rather than crystallinity.
[0039] Application of a high-strength, highly biocompatible, and tough hydrogel as described above in tissue engineering repair, drug delivery, and human site testing.
[0040] Preferably, the tissue includes, but is not limited to, muscle tissue, tendon tissue, skin tissue, nerve tissue, or other motor tissues. Tendon tissue is more preferably preferred.
[0041] Preferably, when using the tough hydrogel for human body part detection, liquid metal is injected into the tough hydrogel, and then the tough hydrogel containing liquid metal is fixed to a designated human body part. The changes in the state of the part are analyzed by detecting the changes in resistance, thereby realizing the detection of the human body part.
[0042] As a further preferred embodiment, the liquid metal includes, but is not limited to, mercury, cesium, gallium, rubidium, potassium, sodium, indium, lithium, and tin. As even more preferred, the liquid metal is Ga. 25 In 75 .
[0043] Preferably, coating the surface of a tough hydrogel with liquid metal can prepare a flexible conductive membrane for electroencephalography (EEG) and electrocardiogram (ECG) detection. This conductive membrane exhibits good conductivity and flexibility.
[0044] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0045] (1) The method for preparing high-strength, highly biocompatible, and tough hydrogels of the present invention is a supplementary method to existing tough hydrogel preparation methods, which expands the existing tough hydrogel manufacturing methods, and is simple to operate and has low additional cost, and has great commercial value.
[0046] (2) The method for preparing high-strength, highly biocompatible, and tough hydrogel of the present invention can prepare a tough hydrogel with highly ordered molecular chain arrangement, stronger binding effect and increased crystallinity. The chemical composition of the crystal domain formed in the process is consistent with the crystal structure. As a rigid and highly functional crosslinking agent, the crystal domain improves the strength and toughness of the hydrogel by delaying the breakage of the single molecular chain through cracking.
[0047] (3) The high-strength, highly biocompatible, and tough hydrogel of the present invention has excellent mechanical properties (tensile strength up to 6.67 MPa, which is 145 times higher than that of the initial hydrogel), excellent biocompatibility, in vivo self-degradability, and similarity to natural tissue components.
[0048] (4) The preparation method of the present invention, combined with 3D printing technology, can produce tissue repair scaffolds with excellent mechanical properties. The tensile strength is as high as 6.5547 MPa, which is 612 times that of untreated 3D printed hydrogel scaffolds.
[0049] (5) The preparation method of the present invention can be combined with 3D printing technology to manufacture customizable, anisotropic, high-strength, high-toughness, and biocompatible specific scaffolds. These specific scaffolds have broad application prospects in tissue repair and drug delivery.
[0050] (6) The tough hydrogel of the present invention can compensate for mechanical transmission and stimulate tendon differentiation, enabling ruptured tendons to recover rapidly within 8 weeks. It is expected to have a better repair and treatment effect on athletes with tendon damage, making it more suitable for medical application scenarios such as tissue engineering and drug delivery.
[0051] (7) The tough hydrogel of the present invention can be injected with liquid metal to make it have the characteristics of sensing deformation and generating corresponding feedback (using a multimeter test head placed on the hydrogel to test the resistance), thereby realizing the function of real-time detection of various parts of the human body. Attached Figure Description
[0052] Figure 1 This is a schematic diagram of the cyclic loading process in Embodiment 1 of the present invention;
[0053] Figure 2In the diagram: A shows a simulated diagram and a physical image of the initial hydrogel cracking and breaking during stretching; B shows a simulated diagram and a physical image of the tough hydrogel cracking during stretching; C shows a comparison of the mechanical properties of the tough hydrogel and the initial hydrogel; D shows the state of the tough hydrogel when it is subjected to a 2kg dumbbell plate.
[0054] Figure 3 In the image: A is a morphological image of the tough hydrogel trained with ammonium sulfate solutions of different concentrations in Example 2; B is an electron microscope image of the tough hydrogel trained with ammonium sulfate solutions of different concentrations; C is a comparison of the mechanical properties of the tough hydrogel trained with ammonium sulfate solutions of different concentrations.
[0055] Figure 4 In the image: A shows the morphology of the tough hydrogels prepared by different cycles in Example 3; B shows the electron microscope images of the tough hydrogels prepared by different cycles; C shows a comparison of the mechanical properties of the tough hydrogels prepared by different cycles.
[0056] Figure 5 In the diagram: A shows the mechanical properties of PDMS, the tough hydrogel (GBTH) prepared in the examples, and the initial hydrogel; B shows the state of the tough hydrogel (GBTH) and the initial hydrogel (Initial) when subjected to the same magnitude of vertical pushing force from sharp tweezers; C shows a comparison of the stress and strain of the tough hydrogel (GBTH) and PDMS.
[0057] Figure 6 In the middle: A is a schematic diagram of the hydrogel scaffold (initial hydrogel) prepared by 3D printing in Example 4; B is a comparison diagram of the water content and tensile strength of the initial hydrogel, the tough hydrogel prepared by cross-linking and then cyclic loading, and the tough hydrogel prepared by cyclic loading and then cross-linking.
[0058] Figure 7 In the image: A is a confocal microscope image showing a significant increase in ITGs (mechanotropic receptors on cell membranes) content after 4 days of simulated muscle contraction using a tough hydrogel; B is a confocal microscope image showing a significant increase in YAP (cytomechanical sensing factor) content after 4 days of simulated muscle contraction using a tough hydrogel; C is a comparison of related gene expression; D is a Western blot analysis result.
[0059] Figure 8 In the image: A is a schematic diagram illustrating the live tendon repair experiment in Example 6; B is a diagram illustrating the intraoperative process of tendon repair in Example 6.
[0060] Figure 9Figure 1 shows the experimental results of using the tough hydrogel prepared in Example 6 for tendon repair in adult rabbits; where: A shows the H&E staining and Masson staining results of different tendon tissues taken at 4 and 8 weeks; B shows the pathological analysis based on H&E staining and Masson staining; C shows the tensile strength of tendons repaired by different hydrogels at 4 and 8 weeks; D shows the expression comparison of the genes col1a1, tnmd, mkx, mmp3, and mmp13 in tendon tissues after 8 weeks of tendon repair by different hydrogels.
[0061] Figure 10 The diagrams show the application experiments of the tough hydrogel prepared in Example 1, after being injected with liquid metal, for whole-body detection, and the analysis of changes in human body state through changes in resistance. Specifically: A is a schematic diagram of real-time whole-body signal monitoring; B is a diagram showing the process of real-time monitoring of micro-expressions caused by emotions when the tough hydrogel injected with liquid metal is connected to the middle of the forehead; C is a diagram showing the tough hydrogel injected with liquid metal fixed on the cheek to sense deformation caused by movement, thus facilitating real-time monitoring of human health; D and E are diagrams showing the gait process of the tough hydrogel injected with liquid metal placed on the heel and sole of the shoe, analyzing the human gait during movement.
[0062] Figure 11 The diagram shows the application experiment of the tough hydrogel prepared in Example 2, after being coated with liquid metal, for electroencephalography (EEG) and electrocardiogram (ECG) monitoring; where A is EEG detection and B is ECG monitoring. Detailed Implementation
[0063] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Unless otherwise specified, the equipment and reagents used in the embodiments and experimental examples are commercially available. The specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.
[0064] Example 1
[0065] A method for preparing a high-strength, highly biocompatible, and tough hydrogel includes the following steps:
[0066] 1. First, prepare a 2% penicillin-streptomycin solution (PSL) using phosphate buffered saline (PBS).
[0067] 2. Add 1g of GelMA hydrogel and 0.04g of LAP to a conical centrifuge tube (50ml), pour in 20ml of PSL solution, and then place the centrifuge tube in a constant temperature water bath at 60℃ until completely dissolved to obtain the hydrogel precursor solution.
[0068] 3. Slowly pour PDMS (polydimethylsiloxane) (monomer and curing agent mixed in a ratio of 10:1 and treated with vacuum defoamer) into the cleaned mold, place it in an oven at 80°C and let it stand for 2 hours, and then drop an appropriate amount of the prepared hydrogel precursor solution into PDMS.
[0069] 4. Place the mold in a refrigerator at 2-8℃ and let it stand for 10 minutes. Then, expose it to blue light for 15 seconds to crosslink and cure. Take out the cured hydrogel to obtain the initial hydrogel (GelMA).
[0070] 5. Prepare two cuboids (without lids), and add appropriate amounts of (NH4)2SO4 (w / v 50%) solution and PBS solution to each.
[0071] 6. According to... Figure 1 The process shown involves completely immersing the cured hydrogel (initial hydrogel) in a (NH4)2SO4 (w / v 50%) solution and stretching it back and forth 20 times at a low speed of 5 mm / min (maximum stretching deformation 100%), followed immediately by immersion in PBS solution for 60 seconds. This constitutes one cycle. Repeating this cycle 20 times yields a tough hydrogel with high strength and high biocompatibility.
[0072] Performance testing:
[0073] Using a universal testing machine and with the same tensile parameters, the mechanical properties of the initial hydrogel obtained in step 4 and the tough hydrogel obtained in step 6 were tested. The tensile rate was set to 5 mm / min, and the tensile stroke variation was 1%–100%. The test results are as follows: Figure 2 As shown in Figures A through C. Figure 2 As can be seen from C, compared with the initial hydrogel, the tough hydrogel (shown as a high-strength hydrogel in the figure) has excellent tensile strength (stress) and elongation at break (strain); and because Figure 2 As can be seen from A and B, the tough hydrogel is significantly better than the initial hydrogel in resisting crack propagation. Figure 2 Diagram D shows the state of the tough hydrogel prepared in this embodiment under the influence of a 2kg dumbbell plate. Figure 2 As can be seen from Figure D, the tough hydrogel prepared in this embodiment has excellent tensile strength and toughness.
[0074] Using a universal testing machine with the same tensile parameters, a tensile rate of 5 mm / min, and a tensile stroke variation of 1–100%, the deformation and mechanical properties of polydimethylsiloxane (PDMS), the initial hydrogel prepared in step 4 (shown as Initial in the figure), and the tough hydrogel prepared in step 6 (shown as GBTH in the figure) under tensile conditions were tested. Figure 5In Figure A, the deformation properties of polydimethylsiloxane (PDMS), initial hydrogel, and tough hydrogel under tensile conditions are tested. Figure 5 C represents the comparison of the mechanical properties of polydimethylsiloxane (PDMS) and tough hydrogel; Figure 5 Diagram B shows the state of polydimethylsiloxane (PDMS) and a tough hydrogel under the same vertical pushing force from sharp tweezers. Figure 5 As can be seen from A and B, compared to the initial hydrogel, the tough hydrogel exhibits a significant increase in tensile strength and elongation at break, and can effectively prevent crack propagation and resist the pushing action of sharp tweezers. From Figure 5 As can be seen from A and C, the tensile strength and elongation of the tough hydrogel are significantly improved compared to PDMS.
[0075] Example 2: Effect of different concentrations of ammonium sulfate solution on tough hydrogels
[0076] The tough hydrogel was prepared according to the method of Example 1, except that different concentrations of ammonium sulfate solution (0%, 40%, 50%, and 60% respectively) were used to stretch the initial hydrogel and four different tough hydrogels were prepared.
[0077] Figure 3 In the figures A and B, respectively, are morphological images and electron microscope images of four different tough hydrogels.
[0078] Mechanical properties were tested on four different tough hydrogels, and the results are shown in [Figure number missing]. Figure 3 C. By Figure 3 As can be seen from the AC results, when the ammonium sulfate solution concentration is too low (≤40%), the hydrogel cannot produce highly oriented hydrogels and high-functional crystalline regions during stretching training; when the ammonium sulfate solution concentration is too high (≥60%), it will lead to excessive water loss of the hydrogel, reducing its quality and affecting its biocompatibility. Therefore, an ammonium sulfate solution concentration of 50% was selected as the optimal stretching training concentration for GelMA hydrogel.
[0079] Example 3: Effect of different number of loading cycles on tough hydrogels
[0080] The tough hydrogels were prepared according to the method in Example 1, except that the number of cycles of loading (stretching training plus PBS solution soaking) of the hydrogels were set to 0, 10, 20 and 30 times, respectively, to prepare four different tough hydrogels.
[0081] Figure 4 In the figures A and B, respectively, are morphological images and electron microscope images of four different tough hydrogels.
[0082] Mechanical properties were tested on four different tough hydrogels, and the results are shown in [Figure number missing]. Figure 4 C. By Figure 4 As can be seen from the AC results, when the number of loading cycles is low (≤10 times), the hydrogel cannot produce highly oriented hydrogels and high-functional crystalline regions during stretching training; when the number of loading cycles is high (≥30 times), it leads to excessive hydrogel formation, reducing the quality of the hydrogel and affecting its biocompatibility. Therefore, 20 cycles were selected as the optimal number of loading cycles for GelMA hydrogels.
[0083] Example 4: Effect of different treatment sequences on tough hydrogels
[0084] like Figure 6 As shown in Figure A, 10 ml of GelMA hydrogel and LAP solution (hydrogel precursor solution prepared in Example 1) were introduced into a 10 cc (mL) dispensing needle. The initial hydrogel bioscaffold printing process was completed according to the preset program to obtain the initial hydrogel scaffold. Three identical printed hydrogel scaffolds were prepared.
[0085] Two of the printed hydrogel scaffolds were placed under blue light for 15 seconds to cure, and the cured hydrogels were removed to obtain the initial hydrogels. One of the initial hydrogels was processed according to steps 5 and 6 in Example 1 to obtain tough hydrogel A (crosslinking + reinforcement).
[0086] The remaining printed hydrogel scaffold was processed according to steps 5 and 6 in Example 1 to obtain tough hydrogel B (reinforced + crosslinked).
[0087] The water content and tensile strength of the initial hydrogel and the tough hydrogels A and B were tested respectively, and the test results are as follows. Figure 6 As shown in A and B. From Figure 6 As shown in Figures A and B, compared to the initial hydrogel (90% water content), although the water content of the hydrogels prepared by cross-linking followed by strengthening (tough hydrogel A, 60.01% water content) and strengthening followed by cross-linking (tough hydrogel B, 67.732% water content) decreased, they still maintained good biocompatibility. However, the tensile strength of tough hydrogel A was 470 times that of the initial hydrogel, and the tensile strength of tough hydrogel B (6.5547 MPa) was 612 times that of the initial hydrogel. Therefore, compared to the initial hydrogel, both tough hydrogel A and tough hydrogel B exhibit significant advantages in overall performance.
[0088] Example 5
[0089] 1) Four tough hydrogels were prepared according to the method in Example 1;
[0090] 2) Inoculate each tough hydrogel with 1×10 6P2 (second generation) TPSCs were cultured and adapted for 24 hours.
[0091] 3) Over the next four days after culture, four tough hydrogels loaded with TPSCs were fixed onto muscle simulators and immersed in a phenol red-free medium (DMEM (medium), GIBCO; 4% FBS (fetal bovine serum), GIBCO) for stretching. The stretching ranges of the four tough hydrogels were 0%, 20%, 50%, and 100%, respectively. Stretching was performed 20 times daily. After four days of training, tendon tissue was harvested for fluorescent staining. The test results are as follows: Figure 7 As shown.
[0092] Depend on Figure 7 As can be seen from Figures A and B, after four days of stretching training, the content of ITGs (mechanotropic receptors on cell membranes) and YAP (cytomechanical sensing factor) in the cell-loaded tough hydrogel increased significantly. Figure 7 The significant increase in the expression of related genes in C and D and the enhancement of protein immunoblotting can also corroborate the above viewpoint; Figure 7 These results demonstrate that tough hydrogels can act as compensating receptors for force transmission, something that primitive hydrogels could not do.
[0093] Example 6
[0094] Initial hydrogels and tough hydrogels were prepared according to the method in Example 1.
[0095] like Figure 8 As shown in Figure A, the rabbit tendon was dissected, and the prepared initial hydrogel and tough hydrogel were sutured to the tendon defect site, respectively. The wound was then sutured and disinfected. The tendon repair process under different treatment conditions is shown in [reference needed]. Figure 8 B. Tissue samples taken at 4 and 8 weeks post-repair with different hydrogels, as well as natural tendon tissue, were subjected to H&E staining and Masson staining analysis, tensile strength testing, and gene expression analysis in the tendon tissue. The analytical results are shown in [see attached image]. Figure 9 .
[0096] like Figure 9 As shown in Figure A, analysis of the stained sections of tendon repaired adult rabbits revealed that when tough hydrogel (shown as high-strength gel in the figure) was used for tendon repair, the newly formed fibers were arranged in a straight line (similar to the collagen morphology of normal tendon (natural tissue)); the fibers formed by the initial hydrogel repair of the tendon were arranged in a wavy pattern and persisted until 8 weeks post-surgery; and the tissue morphology of the tendon repaired by tough hydrogel showed almost no pathological difference from that of normal tendon tissue.
[0097] Depend on Figure 9 As can be seen from B, Figure 9The difference in repair effect shown in the A group persisted for eight weeks after surgery, at which point the tough hydrogel group showed almost no pathological difference in tissue morphology compared to normal tissue after training.
[0098] Depend on Figure 9 As can be seen from C, tendon repair using tough hydrogel resulted in new tendons that were 2-4 times stronger than those in other groups (initial hydrogel-repaired tendons and naturally grown tendons). Figure 9 As shown in C.
[0099] Figure 9 Further analysis of the gene expression level of D in the middle molecule also confirmed this. Figure 9 The experimental results of C showed that the tendon-positive MKX, tnmd and col1a1 genes were upregulated in the tendon tissue repaired by the tough hydrogel prepared in Example 1, which proved that the tough hydrogel prepared in Example 1 can be directly sutured to the rupture site of the tendon in adult rabbits, stimulating the tendon to differentiate rapidly and recover to its initial state.
[0100] Application Example 1
[0101] A tough hydrogel was prepared according to the method in Example 1, and then liquid metal Ga was added. 25 In 75 Inject a tough hydrogel. For example... Figure 10 As shown, tough hydrogels filled with liquid metal can be placed on various parts of the human body, and changes in the body's condition can be analyzed by detecting changes in resistance, enabling comprehensive real-time monitoring of the human body.
[0102] Application Example 2
[0103] A tough hydrogel was prepared according to the method in Example 1. A tough conductive film was successfully prepared by coating the GBTH surface with liquid metal Ga for electroencephalography and electrocardiogram monitoring.
[0104] Figure 11 To achieve good conductivity and flexibility after coating a tough hydrogel surface with liquid metal, it was used to detect electroencephalograms and electrocardiograms in mice.
[0105] In summary, this invention produces a high-strength, highly biocompatible, and tough hydrogel by cyclically stretching the hydrogel in an ammonium sulfate aqueous solution and repeatedly soaking it in PBS buffer. This hydrogel is characterized by its ease of operation, low additional cost, good biocompatibility, and ability to degrade naturally in vivo. It can be directly sutured to the site of tendon rupture in adult rabbits to compensate for the mechanical transmission after tendon rupture and stimulate rapid differentiation and recovery of the tendon to its initial state. Furthermore, it can be used for comprehensive real-time monitoring of the human body. It effectively simulates in vivo tissue structures, making it more suitable for life science and clinical medical research, and possesses enormous application prospects and commercial value.
[0106] The above-described embodiments are merely preferred embodiments of the present invention. It should be noted that the above embodiments are exemplary and should not be construed as limiting the present invention. For those skilled in the art, several changes, modifications, substitutions, and variations can be made without departing from the principle of the present invention, and these improvements and refinements should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a high-strength, highly biocompatible, and tough hydrogel, characterized in that, include: The hydrogel was repeatedly stretched in a sulfate solution and then immersed in a PBS solution. The end of the immersion process was considered as one loading process. The hydrogel is cyclically loaded multiple times according to the aforementioned loading process to obtain the high-strength, highly biocompatible, and tough hydrogel. The hydrogel is one of gelatin and hyaluronic acid; The concentration of the sulfate solution is 40-60%; The hydrogel can be cyclically loaded 10 to 30 times.
2. The method for preparing a high-strength, highly biocompatible, and tough hydrogel according to claim 1, characterized in that, During a loading process: The hydrogel was repeatedly stretched in sulfate solution 10 to 30 times; The hydrogel was soaked in PBS solution for 30-180 seconds.
3. The method for preparing a high-strength, highly biocompatible, and tough hydrogel according to claim 1, characterized in that, The stretching rate of the hydrogel in sulfate solution is 2~7 mm / min.
4. The method for preparing a high-strength, highly biocompatible, and tough hydrogel according to claim 1, characterized in that, The hydrogel may be a cured hydrogel or an uncured hydrogel. When the hydrogel is an uncured hydrogel, after multiple cycles of loading, the treated hydrogel is cross-linked and cured to obtain the high-strength, highly biocompatible, and tough hydrogel.
5. A high-strength, highly biocompatible, and tough hydrogel, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 4.
6. The high-strength, highly biocompatible, and tough hydrogel according to claim 5, characterized in that, The water content of the tough hydrogel is 50-95%.
7. The application of a high-strength, highly biocompatible, and tough hydrogel as described in claim 5 or 6 in the preparation of tissue engineering scaffolds, drug delivery carriers, and human body site testing devices.
Citation Information
Patent Citations
Preparation method and application of high-strength oriented polyvinyl alcohol hydrogel
CN110229374A
Recyclable high-toughness composite hydrogel as well as preparation method and application thereof
CN115570859A
